2012
DOI: 10.1089/ars.2011.4401
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Look at the Chemistry and Biology of Hydrogen Sulfide

Abstract: Significance: Hydrogen sulfide (H 2 S) is garnering increasing interest as a biologically relevant signaling molecule. The effects of H 2 S have now been observed in virtually every organ system and numerous physiological processes. Recent Advances: These studies have not only opened a new field of ''gasotransmitter'' biology, they have also led to the development of synthetic H 2 S ''donating'' compounds with the potential to be parlayed into a variety of therapeutic applications. Critical Issues: Often lost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
180
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(185 citation statements)
references
References 79 publications
(94 reference statements)
3
180
1
1
Order By: Relevance
“…We also found that CMBBH 2 S increased sharply, with a very steep slope, when the rate of H 2 S administration was close to the lethal levels of exposure, corresponding to a CMBBH 2 S around 30 -40 M. Wintner et al (54) also showed, using a series of in vitro studies, that the MBB technique can identify H 2 S present in various forms in the blood. First, H 2 S concentrations in the plasma were similar to the values obtained using amperometry, which only measures soluble H 2 S (15,30,37). We found that in saline, CMBBH 2 S did not change within 10 min, if evaporation of H 2 S was prevented, in keeping with our previous results (49,50).…”
Section: What Was Measured In the Blood?supporting
confidence: 89%
“…We also found that CMBBH 2 S increased sharply, with a very steep slope, when the rate of H 2 S administration was close to the lethal levels of exposure, corresponding to a CMBBH 2 S around 30 -40 M. Wintner et al (54) also showed, using a series of in vitro studies, that the MBB technique can identify H 2 S present in various forms in the blood. First, H 2 S concentrations in the plasma were similar to the values obtained using amperometry, which only measures soluble H 2 S (15,30,37). We found that in saline, CMBBH 2 S did not change within 10 min, if evaporation of H 2 S was prevented, in keeping with our previous results (49,50).…”
Section: What Was Measured In the Blood?supporting
confidence: 89%
“…Low concentrations of H 2 S irritate the eyes, nose, throat, and respiratory system; high concentrations of H 2 S lead to rapid loss of consciousness and death (Evans 1967;Li and Lancaster 2013;Lindenmann et al 2010). Interestingly, this gaseous molecule has been recently classified as a member of the gasotransmitter family, sharing similarities with its congeners nitric oxide (NO), carbon monoxide (CO), and dioxygen (O 2 ) (Vandiver and Snyder 2012;Wang 2012;Li and Moore 2011;Szab o 2007;Kolluru et al 2013;Fukuto et al 2012;Olson et al 2012;Olson 2012). The biosynthesis of H 2 S in mammalian tissues has been attributed to enzymes, including cystathionine β-synthase (CBS), cystathionine γ-lyase (CSE), and 3-mercaptopyruvate sulfur-transferase (3-MST), in combination with cysteine amino transferase (CAT) (Scheme 1) (King 2013;Martelli et al 2012a;Szabo 2012;Paul and Snyder 2012;Hu et al 2011;Prabhakar 2012).…”
Section: Introductionmentioning
confidence: 99%
“…15 The importance of thiol ionization in governing the reactivity via sulfenation followed by reductive polysulfide-forming reactions is illustrated by the fact that increasing the pH from 6 to 8 (ie, the physiological range) increases the oxidation rate of H 2 S 10-fold. 12,19 Although the formation of polysulfides from the reaction of H 2 S with oxygen or H 2 O 2 has been rationalized above in terms of a sulfenic acid intermediate, we have provided no evidence of this mechanism and so alternatives remain possible. As the chelator DTPA did not alter the reaction of H 2 S with oxygen or H 2 O 2 , it is perhaps reasonable to exclude a major role for transition metal impurities, such as iron participating in the oxygen or peroxide-mediated conversion of H 2 S into polysulfides.…”
Section: 18mentioning
confidence: 76%
“…11,12 Such deprotonated thiols can rapidly react with oxidants to form disulfide or polysulfide species, likely via a transient sulfenic acid intermediate. 13 These oxidized variants of H 2 S instead of being reducing agents in fact have oxidant properties that are anticipated to catalyze thiol oxidation via thioldisulfide exchange reactions.…”
Section: Stubbert Et Al H 2 S Via Polysulfides Oxidatively Activates mentioning
confidence: 99%